ANALISA EFISIENSI KOLEKTOR SURYA PLAT DATAR DENGAN DEBIT ALIRAN FLUIDA 3-10 LITER/MENIT - Sulaeman Sulaeman; Darul Mapasid (Jurnal Teknik Mesin (JTM), 2013)
Solar thermal energy is one of the potential energy to be explored and developed further as a source of backup energy. To be able to directly utilize solar thermal energy to heat water can be used in a device that can collectsolar energy to the Earth's surface and convert it back into useful heat energy. This device is called the solarcollector. Solar collectors can be defined as a heat transfer system that generates thermal energy by harnessingthe Sun's radiation as the main source of energy. After testing by varying the flow capacity of 3 litters /minute upto 10 liters/minute, then in the temperature of the fluid can come out (Tout) is the highest of 61,9 C, which ispresent on the stream discharge 7,5 litters/minute. And the highest efficiency in the discharge flow of 5 litters/minute is equal to 86,54%. The results of this test indicate the efficiency of the collector surya.